Exploring the psychological profile of rock climbing athletes participating in the Pekan Olahraga Nasional (PON) in West Nusa Tenggara: A psychometric analysis - Isnaini, Lalu Moh Yudha; Hasbi; Purwanto, Didik; Suharti; Setiawan, Edi (UIR Press, 2023)
Psychological factors are important factors in sports achievement. Psychological training programs in sports have been used in various fields to improve skills. This study uses survey with a test and measurement approach, a type of quantitative descriptive research. The subjects of this study were 8 rock climbing athletes. The instruments used were concentration, anxiety, and confidence. The results of the analysis obtained from the calculation of the psychological profile of the NTB rock climbing athletes are concentration with an average of 10.87, anxiety with an average of 19.50, motivation with an average of 115.87, and confidence with an average of 120.50. The weakest psychological indicator was concentration, while anxiety and self-confidence were average indicators. On the other hand, motivation was a strong point and was categorised as good. There were several limitations to consider in this study. First, this study focused on four psychological factors, namely concentration, anxiety, motivation, and self-confidence, while potentially neglecting other significant aspects of the psychological profile of the athlete. Second, there were only nine participants in the sample, limiting the generalizability of the results. Future research should surmount these limitations by incorporating a broader range of psychological factors and increasing the sample size to produce more exhaustive and representative results. The findings of this study highlight the significance of continuous mental training to enhance the performance of rock climbers. In addition, this study provides practitioners and researchers with a valuable resource for addressing issues related to an athlete's psychological well-being.